EFEKTIVITAS MEDIA PEMBELAJARAN INTERAKTIF FISIKA DALAM MENINGKATKAN KEMAMPUAN LITERASI SAINS PESERTA DIDIK SISTEMATIKA KEPUSTAKAAN - Sari, Kholifa Atika; Putri, Prima Isma; Desnita, Desnita; Usmeldi, Usmeldi; Andriyani, Dwi Rika (EduFisika: Jurnal Pendidikan Fisika, 2024)
This study reviews the literature in an effort to determine how well students' science literacy can be raised by utilizing interactive learning resources for physics. Understanding scientific ideas, using science knowledge in daily situations, and analyzing and resolving science-related issues are all components of science literacy. This study has identified and analyzed a variety of interactive learning media, including interactive magazines, interactive kinematics learning applications, interactive electronic learner worksheet based on LiveWorksheets, Higher Order Thingking Skill-based interactive modules, and learning videos based on the 5E learning cycle model. The study's findings show that interactive learning media can be a very useful tool for teaching physics, but its effectiveness depends largely on how well it is implemented, how well the design of the instruction is done, and how well the learning environment supports the student.